2011
DOI: 10.9741/2161-2978.1052
|View full text |Cite
|
Sign up to set email alerts
|

African-Born Immigrants in U.S. Schools: An Intercultural Perspective on Schooling and Diversity

Abstract: Despite the significant increase of African-born immigrants in the United States of America, the education system does not recognize their presence and does little to facilitate their integration through the implementation of necessary curricular adjustments. The purpose of this article is to call on multicultural education advocates to endorse the argument for the distinctness of Africanborn immigrants as a complex cultural group with unique vulnerabilities requiring sensitivity. Organizationally, the paper d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…What the academy has not been adept at addressing is the heterogeneity within minority populations. Minority populations oftentimes are presented as a whole group based on race, and the unique experiences of various ethnicities and nationalities are oftentimes not taken into account; as Harushimana & Awokoya (2011) note "[t]he multicultural paradigm has yet to frame a multidimensional, culturally-responsive pedagogy, so that the needs and experiences of immigrant groups from societies with an embedded cultural diversity are recognized" (p. 36). One such example is the way in which Asian populations are presented when institutions address diversity.…”
Section: The Perpetual "White Space" In America's Academymentioning
confidence: 99%
“…What the academy has not been adept at addressing is the heterogeneity within minority populations. Minority populations oftentimes are presented as a whole group based on race, and the unique experiences of various ethnicities and nationalities are oftentimes not taken into account; as Harushimana & Awokoya (2011) note "[t]he multicultural paradigm has yet to frame a multidimensional, culturally-responsive pedagogy, so that the needs and experiences of immigrant groups from societies with an embedded cultural diversity are recognized" (p. 36). One such example is the way in which Asian populations are presented when institutions address diversity.…”
Section: The Perpetual "White Space" In America's Academymentioning
confidence: 99%
“…For example, among Nigerians, relatively high economic success may be attributed to pre-migration status as professionals; however, Ethiopians, many who come seeking asylum, arrive with fewer resources and years of schooling (Rong & Preissle, 2009). Regardless of reasons for immigrating or pre-migration status, African immigrants to the United States may be subject to racism that did not exist in home countries (Harushimana & Awokoya, 2011).…”
mentioning
confidence: 99%
“…In addition, they learn new values while in school, but such values are sometimes unfit for the African society. Harushimana and Awokoya (2011) also highlighted a similar challenge. They suggested that education in the US sometimes rids the African international students of any meaningful value to their communities in Africa.…”
Section: Practical Knowledgementioning
confidence: 95%
“…Adopting a multicultural education lens requires special training for the teachers. Harushimana and Awokoya (2011) also recognized the challenge associated with multicultural education. They accept that multicultural education 152 "captures the aspirations and expectations of most immigrant families and their children" (p. 36) but it is difficult to achieve, especially in the US where new immigrants keep coming.…”
Section: Practical Knowledgementioning
confidence: 99%